Identification of small molecule inhibitors of p27Kip1 ubiquitination by high‐throughput screening. Issue 11 (6th September 2013) - Ooi, Li‐Ching; Watanabe, Nobumoto; Futamura, Yushi; Sulaiman, Shaida Fariza; Darah, Ibrahim; Osada, Hiroyuki
Abstract : Dysregulation of p27 Kip1 due to proteolysis that involves the ubiquitin ligase (SCF) complex with S‐phase kinase‐associated protein 2 (Skp2) as the substrate‐recognition component (SCF Skp2 ) frequently results in tumorigenesis. In this report, we developed a high‐throughput screening system to identify small‐molecule inhibitors of p27 Kip1 degradation. This system was established by tagging Skp2 with fluorescent monomeric Azami Green (mAG) and CDK subunit 1 (Cks1) (mAGSkp2–Cks1) to bind to p27 Kip1 phosphopeptides. We identified two compounds that inhibited the interaction between mAGSkp2–Cks1 and p27 Kip1 : linichlorin A and gentian violet. Further studies have shown that the compounds inhibit the ubiquitination of p27 Kip1 in vitro as well as p27 Kip1 degradation in HeLa cells. Notably, both compounds exhibited preferential antiproliferative activity against HeLa and tsFT210 cells compared with NIH3T3 cells and delayed the G1 phase progression in tsFT210 cells. Our approach indicates a potential strategy for restoring p27 Kip1 levels in human cancers.